Play and Propaganda: The Sports of the Ilustrados in Nineteenth-Century Europe - Perez, Micah Jeiel (Archīum Ateneo, 2020)
The adoption of nineteenth-century European sporting practices was a component in the ilustrados’ creation of a national identity. By highlighting the ilustrados’ participation in modernizing individual sports (e.g., gymnastics, fencing, and pistol shooting), thearticle shows how the adoption of foreign sports promised these young men from the Spanish Philippines an opportunity to stand on equal footing with their supposed betters. The constant training of the body was treated as a tool to maintain health, a weapon against vices, and an avenue to achieve excellence in a modern cultural space associated with ideals of masculinity and civilization.KEYWORDS: ILUSTRADO • SPORTS • NATIONALISM • MASCULINITY • MODERNITY